Fluid Inclusion Study Of The Polymetallic Epithermal Quartz Veins At Soripesa Prospect Area, Sumbawa Island, Indonesia - Win Kant; I Wayan Warmada; Arifudin Idrus; Lucas Donny Setijadji; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
The Soripesa prospect area is located at Maria village, Wawo district, Bima region in the eastern part of Sumbawa Island, Indonesia. This area is a part of Cenozoic Calc-alkaline volcanic inner Banda-Sunda Arc. The dominant lithology of Soripesa prospect area are a lithic-crystal tuff of andesitic and dacitic composition and bedded limestone. There have five main polymetallic epithermal quartz veins in the Soripesa prospect area, namely, Rini vein, Jambu air vein, Dollah vein, Merpati vein, and Arif vein. Those quartz veins are hosted mainly in andesitic volcaniclastic rocks. Fluid inclusion study on those quartz veins is vey important to know the condition of hydrothermal fluids and their origin. Fluid inclusion study is conducted at the laboratory of Earth Resources Engineering Department, Kyushu University, Japan. Homogenization temperature, freeze temperature, eutectic temperature, and melting temperature can be known from fluid inclusion study. Based on fluid inclusion study, formation temperatures of all veins are between 250–260◦C. Melting temperature is between -0.2 to -3◦C. Based on the melting temperature, salinity (wt.% NaCl equiv.) of fluid inclusions is calculated by using Bodnar’s equation. Paleodepth of formations and pressure of trapping are also estimated by using formation temperature and salinity. Based on Hass (1971) diagram, estimated paleodepths of formations are 270 m for Merpati vein, 400 m for Dollah vein, 480 m for Rini vein, 570 m for Arif vein, and 680 m for Jambu Air vein, respectively. Pressure of trapping can also be estimated from depth of formation, density of lithostatic overburden, and gravity; 72 bars for Merpati vein, 106 bars for Dollah vein, 127 bars for Rini vein, 151 bars for Arif vien, and 180 bars for Jambu Air vein, respectively. Keywords: Soripesa, polymetallic quartz veins, homogenization temperature, salinity.